2018
DOI: 10.26438/ijsrbs/v5i3.8587
|View full text |Cite
|
Sign up to set email alerts
|

Comparative qualitative profile of various extracellular enzymes produced by two indigenous fungus Lentinus cladopus and Pleurotus pulmonarius

Abstract: White rot fungi are well known prominent and efficient producers of various extra-cellular enzymes that play an essential role in various industries including food, paper, textile, medicine, etc. Therefore, the two important white rot species of Lentinus cladopus and Pleurotus pulmonarius were screened for the qualitative profile of various enzymes on solid medium. The result obtained revealed the remarkable presence of different extracellular enzymes including cellulase, mannanase, xylanase, pectinase, amylas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…All these findings suggest that bacterial degradation of lignin is important than previously thought. But bacteria are not the only source, fungi particularly white rot fungi is the main decomposer of lignin [32]. The number of fungal species which are lignin biodegraders lignin is not known exactly; but Gilbertson reported that there are approximately 1600 to 1700 species of wood-degrading fungi [33].…”
Section: Sources Of Lignin Peroxidasementioning
confidence: 99%
“…All these findings suggest that bacterial degradation of lignin is important than previously thought. But bacteria are not the only source, fungi particularly white rot fungi is the main decomposer of lignin [32]. The number of fungal species which are lignin biodegraders lignin is not known exactly; but Gilbertson reported that there are approximately 1600 to 1700 species of wood-degrading fungi [33].…”
Section: Sources Of Lignin Peroxidasementioning
confidence: 99%